Illustrated key to the genera included in the tribe Acanthocephalini (Hemiptera: Heteroptera: Coreidae: Coreinae), with descriptions of three new genera, seven new species, new taxonomic rearrangements, and a key to genera of Placoscelini - Brailovsky, Harry (Zootaxa, 2021)
Three new genera and seven new species of Acanthocephalini Stål (Hemiptera: Heteroptera: Coreidae) are described: Anomalopetalops with three new species, A. brulei (French Guiana), A. ariquemesus (Brazil), and A. diamantinus (Brazil); Antipetalops with two new species, A. colombianus (Colombia), and A. discretus (Bolivia); and Cryptopetalops with two new species, C. llorentei (Brazil and French Guiana), and C. pluteus (Peru). Dorsal habitus photographs, and keys to the new species of each genus are added. Dorsal habitus photographs and a key to the 18 known genera of Acanthocephalini are given. Placophyllopus Blöte, 1938 is synonymized under Meluchopetalops Breddin, 1903. Placophyllopus cothurnatus Blöte, 1938 is considered a junior synonym of Meluchopetalops banausus Breddin, 1903. Bermejanus Brailovsky, 2018 is transferred to the tribe Placoscelini, and a key to the known genera of that tribe is provided.